The effectiveness of tui na massage on increasing appetite in toddlers who experience difficulty in eating - Lubis, Nur Azizah; Sihombing, Juliana Sion (Institute Of Computer Science (IOCS), 2024)
Difficulty eating in children that is not treated immediately can cause malnutrition, dehydration, underweight, and can interfere with the child's cognitive development. The aim of this research is to see the effectiveness of Tui Na massage in increasing appetite in toddlers at the Elfita Clinic, Medan City. The method used in this research was a quasi experiment with a one group pretest-post test design. Using simple random sampling. Data analysis through the Chi Square test with an alpha significance value of 0.05. The research results show a p value of 0.0000 < ? 0.05. Tui Na massage is effective in increasing appetite in toddlers at the Elfita Clinic, Medan City. The conclusion from this research is that the more regularly you do Tui Na massage, the more your toddler's appetite will increase. And it is hoped that mothers of toddlers will be able and regularly apply this massage.